Sport attainment and proprioception - Han, J.; Anson, J.; Waddington, G.; Adams, R. (International Journal of Sports Science and Coaching, 2014)
Proprioceptive ability specific to the movement challenges of a sport was hypothesised to relate to both years of sport-specific training and the competition level that a sport performer has reached. To test this hypothesis, proprioceptive sensitivity on an ankle movement discrimination test was obtained for one hundred athletes at different competition levels, and twenty non-sport-specific, healthy controls. All athletes were without significant injuries during the prior 6 months, preferred to use their right foot, had a minimum of two years sport-specific training (mean 8.7 years), and were actively competing in football, swimming, badminton, sports dancing and aerobic gymnastics. Test scores were higher for athletes than controls (p < 0.005) but not significantly different between sports groups. Within combined sports groups, ankle proprioception scores were significantly correlated with sport competition level attained (rho = 0.45, p < 0.001), but not with years of sport-specific training. Logistic regression analysis demonstrated that ankle proprioception score (p = 0.001) and years of training (p = 0.009) were the two significant predictors in an equation that could successfully classify 80% of the athletes as top-level or lower, highlighting the importance of good ankle proprioception in athlete success. Ankle movement proprioception testing may be useful in talent identification, particularly in sports with a higher level of lower limb demand, and may assist in the identification of athletes who require specifically targeted training to improve their ankle proprioceptive abilities to values associated with the highest-level competitors.